Organizational safety climate and adherence to standard precautions among dentists - Vivan Ribeiro, Patricia Helena; Brevidelli, Maria Meimei [UNESP]; Veiga Tipple, Anaclara Ferreira; Ribeiro, Renata Perfeito; Gir, Elucir (Univ Fed São Paulo, Dept Enfermagen, 2013)
Objective: Check the perception of dentists about safety climate at work in relation to adherence to standard precautions.Methods: It is a quantitative, cross-sectional study conducted through the application of the Safety Climate Scale to a population of 224 dentists who worked in units of primary health care in six municipalities of Parana.Results: The total score of 3.43 (SD = 0.88) reveals that dentists have a poor perception of the incentives and organizational support for adopting standard precautions.Conclusion: Unsatisfactory safety climate, where the perception of dentists about safety in their work environment is deficient, demonstrating fragile management actions of support to safety, lack of a training program in occupational health and deficient feedback to favor the adoption of safe practices.
Keywords: Organizational culture; Universal precautions; Occupational health nursing; Public health nursing; Primary care nursing